The Penrod score: a prognostic instrument to balance an increasing geriatric fracture caseload with diminishing health care resources? - Müller, Sebastian; Beckmann, Nicholas A. (Archives of orthopaedic and trauma surgery, 2016)
IntroductionGeriatric hip fracture patients are a highly heterogeneous collective, what distinctly aggravates the best possible treatment. Consequently, it is becoming more important to identify selection criteria that can distinguish those patients who can benefit the most from treatment in a geriatric fracture center. In our pilot study, we assessed the 2007 published Penrod score for its utility as a useful selection tool by prospectively comparing our own patient’s outcome with the Penrod study.Methods77 patients treated for geriatric hip fracture were preoperatively classified according to the Penrod score. Patients were divided into three clusters by age (1: <75 years, 2: 75-84 years, 3: ≥85 years). Clusters 2 and 3 were then classified according to their ability to perform activities of daily living (ADL’s) and cognitive status (presence or absence of dementia). In 51 out of these 77 patients, the ability to perform ADLs could be assessed 6 months postoperatively and was compared with the Penrod scores.Results58 % of cluster 1 patients were able to perform 4 ADLs independently 6 months postoperatively (52.9 % Penrod study). In clusters 2A and 3A, 48 and 50 %, respectively, were able to perform 4 ADLs independently, compared with 40.6 and 31.5 % (Penrod collective). 22 % of our patients in 2B performed all ADLs independently (3.6 % Penrod) and 25 % in cluster 3B (9.4 % Penrod).ConclusionOur preliminary results support the prognostic value of the Penrod score in the treatment of geriatric hip fracture patients. With the help of the Penrod score, it may be possible to identify patients, who are expected to significantly profit from an intensified treatment in a geriatric fracture center (clusters 2B, 3A, and 3B). By utilizing this score, improved outcomes and simultaneously a more effective utilization of valuable health care resources could be achieved.